(untitled) (CIPEEX, 2025)
Introduction: Anxiety is a normal human emotion, however, sometimes it can become excessive and take on a pathological meaning, becoming a psychiatric disorder and causing harm to the individual’s life. Therefore, it is important to analyze how to identify, seek help, its possible treatments and consequences. People who present symptoms suggestive of anxiety in an exaggerated way should seek a psychiatrist for an evaluation. Objective: To analyze the development of anxiety in students during the COVID-19 pandemic. Methodology: The methodology involved a detailed search of articles in the PubMED and Google Scholar databases, using the descriptors "Anxiety", "Medical Students" and "Pandemic COVID 19" with the Boolean "and", resulting in 92 studies, and selecting 5 relevant ones after inclusion criteria based on the objective. Articles in English 2024 were selected. Discordant literature was excluded. Results and discussion: All five studies report an increase in anxiety related to COVID-19, with the exception of one that observed a decrease in anxiety levels at the end of the pandemic. Anxiety is more prevalent among women. In addition to the psychological effects, the pandemic also caused significant behavioral impacts on students, including an increase in the incidence of other mental disorders. Final considerations: COVID-19 increased anxiety levels both during the pandemic and, in some cases, after its peak. Two studies identified several risk factors associated with this increase, highlighting the additional impact of the pandemic. Furthermore, students generally have higher rates of mental health problems compared to the general population.